2022
DOI: 10.3390/f13111754
|View full text |Cite
|
Sign up to set email alerts
|

Residents’ Preferences to Multiple Sound Sources in Urban Park: Integrating Soundscape Measurements and Semantic Differences

Abstract: Urban parks provide their residents with a space for activities and interactions, and soundscapes play an important role in influencing the residents’ sense of experience of the park environment, with the result that the preferences of residents regarding multiple sound sources can be used as the basis of improving the soundscape quality and optimizing the function of urban parks. Using Shanghai Century Park as the research area, this study focused on the residents’ preference to multiple sound sources based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Based on audio recordings containing implicit information in soundscapes, Thorogood et al (2016) established the background and foreground classification task within a musicological and soundscape context. For urban park soundscapes, Gong et al (2022) introduce the concepts of "importance" and "performance" and position the soundscape elements in this twodimensional plane. The importance dimension reflects to what extent a particular sound is an essential part of this soundscape.…”
Section: Introductionmentioning
confidence: 99%
“…Based on audio recordings containing implicit information in soundscapes, Thorogood et al (2016) established the background and foreground classification task within a musicological and soundscape context. For urban park soundscapes, Gong et al (2022) introduce the concepts of "importance" and "performance" and position the soundscape elements in this twodimensional plane. The importance dimension reflects to what extent a particular sound is an essential part of this soundscape.…”
Section: Introductionmentioning
confidence: 99%
“…Though individual differences may exist, natural sounds in urban green spaces such as birdsong, cicadas, flowing water, and the sound of breeze blowing through leaves have positive benefits and contribute significantly to soothing stress ( Zhong et al, 2023 ). In a study focusing on residents’ preferred sound sources in urban parks, researchers found that all types of residents had a high preference for natural sounds, especially the elder group ( Gong et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%